2020
DOI: 10.1111/1744-7941.12268
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of work–life balance practices

Abstract: The current study uses a multilevel analysis to examine how work–life balance (WLB) practices applied at the organizational level associate with WLB practices and performance appraisal at the individual level that affects employee commitment, underpinned by the theory of supportiveness and the relational perspective. Respondents were 319 employees and 74 managers from small and medium‐sized enterprises (SMEs) of various industries in Malaysia. Results indicate that the consistency of employee perception of WLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…Moreover, these practices aim to reduce employees' work-life conflict and increase their ability to simultaneously and pragmatically manage their work and family responsibilities [9,17]. Organisations also adopt WLB practices to improve employees' job satisfaction, organisational commitment [9,10], and intention to stay and mitigate their stress [30], workfamily conflict, and, ultimately, turnover intention [11]. Although implications of WLB practices are well espoused in the current academic literature, the main emphasis has been on actual and implemented WLB practices.…”
Section: Work-life Balance Practices Person-job Match and Turnover Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these practices aim to reduce employees' work-life conflict and increase their ability to simultaneously and pragmatically manage their work and family responsibilities [9,17]. Organisations also adopt WLB practices to improve employees' job satisfaction, organisational commitment [9,10], and intention to stay and mitigate their stress [30], workfamily conflict, and, ultimately, turnover intention [11]. Although implications of WLB practices are well espoused in the current academic literature, the main emphasis has been on actual and implemented WLB practices.…”
Section: Work-life Balance Practices Person-job Match and Turnover Intentionmentioning
confidence: 99%
“…Most recently, the focus has been on the role of work-life balance practices in alleviating employees' turnover intention. In this regard, several studies have concluded that work-life balance (WLB) practices exert a significant influence on employees' turnover intention [9][10][11]. While WLB practices are certainly important, recent studies have suggested that the effectiveness of mere provisions of WLB practices do not necessarily guarantee success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadly, most superiors and organizations fail to accept that work and life are intertwined, making it necessary to balance work and life to enhance employee well-being. Most superiors consider work-life balance (WLB) a fad and choose to turn a blind eye towards this balance (Koon, 2020;Mukherjee, 2019). The failure to acknowledge the pertinence of WLB and extend the necessary support sends a negative message to employees.…”
Section: Introductionmentioning
confidence: 99%
“…This theory posits that employees weigh their value in the organization through the support rendered within their organization (Kurtessis et al, 2017). The degree to which organizations provide support to employees reflects how much the organization values them as an employee and are concerned about their well-being (perceived organizational support) (Koon, 2020;Kurtessis et al, 2017). Therefore, when organizations fail to care about employees' need for WLB and provide the required support, employees view the organization in a negative light.…”
Section: Introductionmentioning
confidence: 99%